(untitled) (Northern International Medical College Journal, 2015)
Objective : To assess pattern and proportion of physical abuse during pregnancy in relation to socio demographic characteristics of abused women. Material & Methods : A descriptive type of cross sectional study was conducted in RADDA-MCH-FP Center, Mirpur-10, Dhaka during January to July 2011. A total of 139 pregnant women of reproductive age group (15-45) years who visited for antenatal check up were selected purposely. Data were collected through face to face interview using pretested structured questionnaire. Results : Socio demographic characteristics of respondents revealed that mean age 22.20 ± 39 years and husbands mean age 28.57 ± 5.39 years. Highest number of respondents education upto SSC level (49.6%). 74.8% were housewife; socio economic status was lower middle class, 18.7% had history of dowry. The proportion of physical abuse during pregnancy was 31.6%. Among them 15.83% had mixed type of abuse. Highly significant association was found with dowry (p 0.00) and planed pregnancy (p 0.006). A statistically significant association was found between respondents education level and physical abused (p<0.05) indicating respondents had low level of education increase physical abuse. A statistically significant association also found with residence (urban/slum) (p<0.05) and who had history of dowry (p<0.05). Conclusion : Physical abuse during pregnancy was mostly seen in the respondent who belongs to slum area and had low educational level. Therefore necessary step should be taken by health system as well as government to prevent physical abuse during pregnancy. Northern International Medical College Journal Vol.5(1) 2013: 313-315